Adiponectin and Risk of Vascular Events in the Northern Manhattan Study - Gardener, Hannah (2012)
OBJECTIVES: Despite adiponectin’s independent relationship with many markers of vascular disease risk, its association with clinical outcomes is unclear and results of studies have been inconsistent. We examined the association between adiponectin, an adipocytokine secreted by adipose tissue, and vascular events (stroke, myocardial infarction (MI), vascular death) in the multi-ethnic prospective population-based Northern Manhattan Study (NOMAS). METHODS: Adiponectin was measured at baseline among 2900 participants free of MI and stroke (mean age 69±10 years, 37% men, 21% white, 53% Hispanic, 24% black). Over a mean 10 years follow-up, 692 incident vascular events accrued. RESULTS: The mean adiponectin=11.4±6.2 μg/ml (median=9.8, range=2.1–53.3). In Cox models adjusting for demographics and vascular risk factors, a decreased risk of vascular events was suggested with lower adiponectin. Examination of quartiles suggested a non-linear relationship, with a reduction in risk observed among those in adiponectin quartiles 1–3 vs. 4, and the lowest effect estimates observed in quartile 2. Similar results were found when stroke, MI, and vascular death were examined separately. We saw no effect modification by baseline vascular health profile, but the positive association between adiponectin and vascular events was stronger among those with elevated waist circumference. CONCLUSIONS: In NOMAS, low-moderate adiponectin was associated with a decreased risk of vascular events despite the fact that low adiponectin levels were associated with an elevated vascular risk profile. These counter-intuitive findings underscore the need for further research on adiponectin as a useful biomarker of vascular disease risk and mechanisms explaining the inconsistent observations in the literature.